Comparative analysis of IEEE 802.11g multimedia multicast performance using RTP with an implemented test-bed - Ezani, Muhammad Faheem Mohd; Pathan, Al-Sakib Khan; Haseeb, Shariq (2012)
In network layer protocols, the most efficient way of sending similar packets to a group of nodes is via multicast. Multicast is a profound concept that has been around for some time and has seen through its implementation in various aspects of today’s network access technology. The IEEE 802.11 wireless standards, however, loosely honor IP layer multicast packets by encapsulating them in broadcast frames. This in turn degrades the 802.11 network access bandwidth capacity and further decreases its data transmission reliability. An enhancement workaround which has been devised was to encapsulate multicast packets in a unicast MAC layer frame. In addition, RTP was also observed to be an enabler to better user experience in multicast streaming. In this paper, we investigate the 802.11g multicast performance with and without the enhanced multicast mechanism. We further expand our investigation by implementing RTP during the multimedia multicast stream and without it. Our results lead us to conclude that there are significant advantages of using both the enhanced multicast mechanism and RTP during a multicast streaming via the 802.11g wireless standard.